Perspectives on Care for Late-Stage Parkinson’s Disease - Kristina Rosqvist; Marianne Kylberg; Charlotte Löfqvist; Anette Schrag; Per Odin; Susanne Iwarsson (Parkinson's Disease)
In the late stage of Parkinson’s disease (PD), there is an increasing disease burden not only for the patients but also for their informal caregivers and the health and social services systems. The aim of this study was to explore experiences of late-stage PD patients’ and their informal caregivers’ satisfaction with care and support, in order to better understand how they perceive the treatment and care they receive. This qualitative substudy was part of the longitudinal European multicentre Care of Late Stage Parkinsonism (CLaSP) project. Individual semistructured interviews were conducted with patients (n = 11) and informal caregivers (n = 9) in Sweden. Data were analysed through the content analysis technique. The final analyses generated one main category: “We are trying to get by both with and without the formal care” and five subcategories: “Availability of health care is important for managing symptoms and everyday life”; “Dependence on others and scheduled days form everyday life”; “There is a wish to get adequate help when it is needed”; “Mixed feelings on future housing and respite care”; and “Family responsibility and loyalty for a functioning everyday life”. Having regular contact with PD-specialised health care was perceived as important. Greater access to physiotherapy was wished for. Maintaining autonomy was perceived as important by patients, in both home health care and a future residential care setting. Responsibility and loyalty between spouses and support from children enabled everyday life to carry on at home, indicating a vulnerability for those without an informal caregiver. The results suggest that regular access to PD-specialised health care is important and that a specialised and multidisciplinary approach to the management of PD symptomatology is likely necessary. Non-PD-specialised staff in home health care and residential care facilities should regularly be given opportunities to obtain PD-specific education and information.